Strategic Management of School Principals in Implementing Deep Learning: A Case Study of Indonesian Elementary Education - Kadek Marsela Yustini Resintia; Rizal Rizal; Surahman Wilade; Nashrullah Nashrullah; Muhammad Nazimuddin Al Kamil; Sisriawan Lapasere (Journal of Innovation and Research in Primary Education, 2026)
Deep learning implementation requires strong strategic leadership, yet limited empirical evidence exists on how principals manage this process in resource-constrained primary schools. This qualitative case study examined strategic management practices of the principal at SD Inpres Perumnas Palu in implementing deep learning. Data were collected through semi-structured interviews with the principal and two teachers, a 25-item Likert-scale questionnaire administered to 31 students, and document analysis. Data analysis followed Miles, Huberman, and Saldaña's interactive model involving data reduction, display, and conclusion drawing. Findings revealed systematic strategic management across three phases: planning through vision-mission alignment and cascade training models (mean effectiveness: 94.8%), implementation via pedagogical guidance and resource mobilization including ATM curriculum adaptation and multi-format supervision, and evaluation through weekly collaborative meetings and systematic monitoring using 15-indicator instruments. Student perceptions indicated predominantly positive deep learning experiences (overall mean = 3.61), with highest scores in mindful learning (mean = 3.76) and joyful learning (mean = 3.71) dimensions. Challenges included ICT competency variations, time constraints, and infrastructure limitations. Strategic management effectively enabled deep learning implementation despite resource constraints, with principal leadership creating conditions supporting pedagogical innovation. The study demonstrates how transformational leadership translates into concrete strategic processes, contributing frameworks for implementing curriculum reform in developing educational contexts.